Semen Parameters Can be Used as a Credible Marker with Doppler Ultrasonography in the Diagnosis of Subclinical Varicocele Cases - Irez, Tulay; Sarikaya, Bahar; Erguven, Mine; Salabas, Emre (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVES: The link between varicoceles and male infertility has been a problem of debate for more than half a century. A substantial amount of data about varicocelectomies’ effects has been provided, but inadequate study designs and heterogeneity of current studies make these data rarely conclusive. This article investigates whether semen and sperm analysis in subclinical varicocele patients without any clinical signs diagnosed by Doppler Ultrasonography (USG) can be used as a diagnostic tool. STUDY DESIGN: The current prospective cohort study included infertile male patients (n=44) enrolled in the Urology Clinic of Biruni University Hospital from January 2017 to January 2018. Patients were divided into two groups: 1st group as the control group (CG) (n=22): No varicocele as determined by Doppler USG, and 2nd group as the test group (TG) (n=22): Subclinical varicocele (SCV) as determined by Doppler USG. A semen analysis was done. Sperm were dyed with aniline blue and chromomycin A3 (CMA3), acridine orange (AO), propidium iodide (PI), and Rhodamine 123 (Rh123) for the determination of sperm maturation, sperm DNA fragmentation, apoptosis, and sperm mitochondrial membrane potential, respectively. Student-t Test was used for statistical analysis. p<0.05 was considered significant. RESULTS: The sperm concentration of the CG was higher than the TG (p=0.98, p>0.05). Forward sperm motility in the CG was higher than in the TG (p<0.001, p<0.05). Sperm with normal morphology in the TG was lower than in the CG (p<0.001, p<0.05). Sperm neck anomalies were higher in varicocele cases (p<0.001, p<0.05). Sperm maturation at the TG was lower than the CG (p<0.001, p<0.05). A high apoptotic sperm rate was found at the TG (p<0.001, p<0.05). Sperm mitochondria potential at the TG was lower than the CG (p<0.001, p<0.05). Sperm chromatin condensation at the TG was higher than the CG (p<0.001, p<0.05). CONCLUSIONS: The analysis of sperm DNA and apoptosis in SCV cases can be used as a reliable diagnostic tool to confirm Doppler USG.